Husserl and the Theological Question - James G. Hart (Eidos. A Journal for Philosophy of Culture, 2018)
Defending the ancient thesis, that being and the true, or being and manifestation, are necessarily inseparable, is at the heart of transcendental phenomenology. The transcendental “reduction” disengages the basic “natural” naïve doxastic belief which permits the world to appear as essentially indifferent to the agency of manifestation. The massive work of transcendental phenomenology is showing the agency of manifestation of “absolute consciousness.” Yet the foundations of this agency of manifestation are pervaded by issues which, when addressed, reveal that the question of a “second absolute” is basic and opens Husserlian phenomenology to metaphysical questions. This has to do not merely with the teleology of the agency of manifestation, i.e., the “whither” of the teleology of presencing, but also, in some sense, with the constituting “whence” of the transcendental I. Husserl argues for the teleology of truth pointing to both a divine subject as well as a divine entelechy.